K-means Clustering Algorithm for Dengue Disease Detection using Tanagra Tool - Yogapriya, P; Geetha, P (International Journal of Computer Sciences and Engineering, 2019)
Dengue disease caused over the tropical and sub-tropical area which spread by Aedes mosquitoes. Dengue has to turn into a severe healthiness problem occurs frequently in the humid and sub-tropical region. The scientists use the data mining algorithm for preventing and protecting different diseases like Dengue disease. This analysis of the attack of Dengue fever in different districts mainly Puducherry, Tamil Nadu. This paper helps to apply the algorithm for clustering of Dengue fever. After that, the construction of the clustering algorithm depends on the graph-based dataset. The K-Means clustering algorithm is applied to detect Dengue fever.